MENINGKATKAN KETERLIBATAN SISWA MELALUI PEMANFAATAN SUMBER BELAJAR LOKAL - Ana Soviana; Annisa Putri Maulida; Intan Putri Dwi Kurniawati (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Increasing student involvement in the learning process is one of the main goals in education. Utilizing local learning resources that include cultural potential, traditions and the surrounding environment is a strategic approach to achieving this goal. This research aims to explore how local learning resources can increase student engagement through relevant and meaningful learning. Where the method used isliterature study. The results show that local learning resources that include culture, traditions and the surrounding environment can increase student participation and strengthen feelings of love for the culture and surrounding environment.